Moving to accelerated protocols of tDCS in catatonia: a case report - Bouaziz, Noomane; Luisada, Jean-Charles; Jabri, Samir; Andrianisaina, Palmyre S.-K.; Bellis, Avicenne; Januel, Dominique (Frontiers in Psychiatry, 2023)
Catatonia is a severe and potentially life-threatening neuropsychiatric condition. Electroconvulsive therapy (ECT) is the gold standard second-line intervention for catatonia after benzodiazepine failure. However, the access to ECT can be particularly challenging, especially during periods of increased strain on medical facilities, such as the COVID-19 pandemic. Several case reports have suggested the potential efficacy of transcranial direct current stimulation (tDCS) in addressing catatonia. In our case, we present the successful application of intensive tDCS, delivering five sessions per day, each lasting 20 minutes, with an intensity of 2mA. The tDCS montage involved placing the anode on the left dorsolateral prefrontal cortex (DLPFC) and the cathode on the left temporoparietal junction (TPJ). This approach was well-tolerated and resulted in a significant improvement in a 70-year-old patient with catatonia, for whom ECT was deemed necessary. While these results are promising, it is crucial to confirm them through a randomized controlled study.